Revision of a Fractured Uncemented Revision Stem Using a Custom Designed Punch and Retrograde Through-Knee Approach - P. J. Nasr; G. S. Keene (Case Reports in Orthopedics)
We report a unique case of a fractured modular cobalt chromium connection taper Revitan (Zimmer, Warsaw, IN) revision prosthesis. Macroscopic examination revealed a fracture at the diaphyseal-metaphyseal junction of this modular component. This report highlights that fractures can still occur with modern modular prostheses. We are not aware of any published failures of the Revitan revision prosthesis. We also describe a unique method of retrieval for a broken well fixed uncemented femoral stem, using a custom designed extraction instrument via a through-knee approach.